The Great Plains : A Fire Survey - Pyne, Stephen J., 1949- (Book collections on Project MUSE., 2017)
"Provides a wide look at plains wildland fire in the 21st century and how it is interconnected with other themes of life and culture in the Midwest"--Provided by publisher.